Pro-poor HPAI risk reduction strategies: Synthesis of country background papers - Tiongco, Marites (International Food Policy Research Institute, 2009)
This brief is a synopsis of five country background papers that provided an inventory of information about the importance of the poultry sector in the economy and for rural livelihoods, the structure of the poultry sector and the associated level of biosecurity, and the threats and incidences of highly pathogenic avian influenza (HPAI), along with prevention and control measures that were implemented and the institutional response capacity (See Alemu et al. 2008, Aning et al. 2008, Obi et al. 2008, Omiti and Okuthe 2008, and Sumiarto and Arifin 2008 for more details). The countries investigated were Ethiopia, Ghana, Indonesia, Kenya, and Nigeria. Incidences of HPAI outbreaks in the world have continued since the first confirmed one in 2003. The virus is still circulating and remains a threat to public health. In 2006, a total of 47 countries reported HPAI in their domestic poultry, with repeated outbreaks in Bangladesh, China, Thailand, and Vietnam. It is considered endemic in several countries, including two that were studied: Indonesia and Nigeria. (See Table 1.) The endemic nature of the disease in these countries constitutes a permanent source of potential contamination for humans and could also be a source of contamination for other countries through legal and illegal movements of animals.